2018
DOI: 10.18632/oncotarget.24324
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of protein-L-isoaspartate (D-aspartate) O-methyl-transferase expression under endoplasmic reticulum stress promotes epithelial mesenchymal transition in lung adenocarcinoma

Abstract: A prognostic association between the novel chaperone protein-L-isoaspartate (D-aspartate) O-methyltransferase (PIMT) and lung adenocarcinoma has recently been reported. Here, we evaluated the functional roles of PIMT in the progression of lung adenocarcinoma. PIMT expression was detectable in 6 lung adenocarcinoma cell lines: A549, H441, H460, H1650, Calu 1, and Calu 6 cell lines. In A549 and H441 cells, knockdown by PIMT using silencing RNA of PIMT (si-PIMT) and/or small hairpin-RNA (sh-PIMT) induced a decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
0
7
0
1
Order By: Relevance
“…The role of ER stress in EMT is somewhat controversial. Huang et al (21) demonstrated that pterostilbene-induced ER stress could inhibit EMT in breast cancer, and recent studies have pointed to a relationship between the TGF-β/Smad signaling pathway and ER stress in a number of cell lines, including A549 cells and podocytes (19,38) suggesting that TGF-β1 can activate ER stress to promote the process of EMT. The present study demonstrated that HP-β-CD could block both the TGF-β/Smad signaling pathway and EMT, revealing a positive association between TGF-β/Smad signaling pathway and EMT, in line with the studies of Moon et al (38) and Yamashita et al (19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of ER stress in EMT is somewhat controversial. Huang et al (21) demonstrated that pterostilbene-induced ER stress could inhibit EMT in breast cancer, and recent studies have pointed to a relationship between the TGF-β/Smad signaling pathway and ER stress in a number of cell lines, including A549 cells and podocytes (19,38) suggesting that TGF-β1 can activate ER stress to promote the process of EMT. The present study demonstrated that HP-β-CD could block both the TGF-β/Smad signaling pathway and EMT, revealing a positive association between TGF-β/Smad signaling pathway and EMT, in line with the studies of Moon et al (38) and Yamashita et al (19).…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al (21) demonstrated that pterostilbene-induced ER stress could inhibit EMT in breast cancer, and recent studies have pointed to a relationship between the TGF-β/Smad signaling pathway and ER stress in a number of cell lines, including A549 cells and podocytes (19,38) suggesting that TGF-β1 can activate ER stress to promote the process of EMT. The present study demonstrated that HP-β-CD could block both the TGF-β/Smad signaling pathway and EMT, revealing a positive association between TGF-β/Smad signaling pathway and EMT, in line with the studies of Moon et al (38) and Yamashita et al (19). However, in contrast to these reports, the present study found that HP-β-CD could induce ER stress to attenuate the EMT, indicating a negative association, and this is in line with Huang et al (21) and Dasgupta et al (39) who found that pterostilbene and AECHL-1 suppressed the EMT by activating ER stress in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we demonstrated that PIMT isoform 1 could regulate oncogenic features such as migration, invasion, and adhesion in U-87 MG glioma cells, and that this isoform was able to modulate cell morphology by remodelling F-actin and microtubule polymerization [ 10 ]. Other studies have reported that PIMT could regulate the expression of EMT markers in MDA-MB-231 breast cancer cells [ 7 ], in BUI-87 and SW780 bladder cancer cells [ 19 ], and in different lung adenocarcinoma cell lines [ 20 ]. Thus, these observations led us to investigate whether PIMT could be involved in EMT processes dependent on TGF-β1 when U-87 MG cells were treated with this cytokine.…”
Section: Resultsmentioning
confidence: 99%
“…D-аспартат, накапливающийся в составе белков при длительной инкубации, может оказывать негативное влияние на их функциональную активность. Это подтверждается тем, что функционирование L-изоаспартат DL-аспартат О-метилтрансферазы (конвертирует D-аспартат в L-форму) является критичным для нормального деления и дифференцировки клеток [10].…”
Section: экспериментальная медицинаunclassified